Identification of two novel mutations in RASGRP2 affecting platelet CalDAG-GEFI expression and function in patients with bleeding diathesis. (17th February 2018) - Sevivas, Teresa; Bastida, José María; Paul, David S.; Caparros, Eva; Palma-Barqueros, Verónica; Coucelo, Margarida; Marques, Dalila; Ferrer-Marín, Francisca; González-Porras, José Ramón; Vicente, Vicente; Hernández-Rivas, Jesús María; Watson, Steve P.; et al.
Abstract: The RASGRP2 gene encodes the Ca 2+ and DAG-regulated guanine nucleotide exchange factor I (CalDAG-GEFI), which plays a key role in integrin activation in platelets and neutrophils. We here report two new RASGRP2 variants associated with platelet dysfunction and bleeding in patients. The homozygous patients had normal platelet and neutrophil counts and morphology. Platelet phenotyping showed: prolonged PFA-100 closure times; normal expression of major glycoprotein receptors; severely reduced platelet aggregation response to ADP and collagen (both patients); aggregation response to PAR1 and arachidonic acid markedly impaired in one patient; PMA-induced aggregation unaffected; platelet secretion, clot retraction, and spreading minimally affected. Genetic analysis identified two new homozygous variants in RASGRP2 : c.706C>T (p.Q236X) and c.887G>A (p.C296Y). In both patients, CalDAG-GEFI protein was not detectable in platelet lysates, and platelet αIIbβ3 activation, as assessed by fibrinogen binding, was greatly impaired in response to all agonists except PMA. Patient neutrophils showed normal integrin expression, but impaired Mn 2+ -induced fibrinogen binding. In summary, we have identified two new RASGRP2 mutations that can be added to this rapidly growing form of inherited platelet function disorder.